Effect of Sodium Hydroxide (NaOH) in Bitumen Separation Process from Asbuton in Hot Wate - Hamzah, Afan; Ferdiansyah, Dita Ahmeta; Nurkhamidah, Siti; Taufany, Fadlilatul; Susianto, Susianto (Institut Teknologi Sepuluh Nopember, 2015)
Hot water process is one of methods to separate bitumen from asbuton. For increasing %recovery of bitumen, we can modify the hot water process by adding diesel oil, sodium hydroxida (NaOH) and Sodium Ligno Sulfonat (SLS) as surfactant. This research was foccusing on effect of the addition of NaOH concentration. This research used asbuton from Kabungka and carried out in two processes, digestion and sedimentation process. % recoverey decreases with the increasing of NaOH concentration. The highest % recovery is 92% when ratio of diesel oil:asbuton 60:40, 0,5%wt SLS concentation, 30%wt SLS-NaOH solution from total solution and 1%wt NaOH concentration.